Intergenerational transfers and home ownership outcomes: Transmission channels and geographic differences. Issue 1 (19th October 2022) - Ong ViforJ, Rachel; Clark, William A. V.; Phelps, Christopher
Abstract: Previous research has shown that the home ownership status of parents matters for the likelihood of a child becoming an owner, and other research has studied how financial intergenerational transfers affect the transition to ownership. We extend these existing studies by estimating the effect of financial transfers on the probability of becoming an owner as well as the role of in‐kind transfers. We also analyse how the impacts of different intergenerational transmission channels vary across neighbourhoods of advantage and disadvantage and discuss the implications for inequality in access to ownership. Drawing on a large panel data set from the Household, Income and Labour Dynamics in Australia Survey, we offer three new findings. First, we show that financial transfers made concurrently with home purchases play a more important role than lagged transfers and that in‐kind transfers are also an important part of the process of gaining ownership. Second, we note that in‐kind transfers are more effective for raising home ownership prospects in areas with high socioeconomic status, while financial transfers appear to be more effective in middle‐class neighbourhoods. Third, children from disadvantaged backgrounds are least likely to be assisted into home ownership by intergenerational transfers.